The protective effect of kiwi fruit extract against to chromium effect on protein expression in Saccharomyces cerevisiae - Aslan, Abdullah; Gok, Ozlem; Erman, Orhan (Mattioli 1885, 2017)
In this study, five groups were composed. i: Control group, ii: K2Cr2O7 group, iii: 10 mM K2Cr2O7+ kiwi juice (KWJ) group, iv: 20 mM K2Cr2O7+ KWJ group, v: 25 mM K2Cr2O7+ KWJ group. After sterilization, fruit juice (20%) and K2Cr2O7 were added different concentration to Saccharomyces cerevisiae (S. cerevisiae) cultures and the cultures were growned at 30 degrees C for 1h, 3h, 5h and 24 hours [overnight (ON)]. S. cerevisiae cell growth was determined by spectrophotometer, total protein changes was detected by SDS-PAGE electrophoresis and reckoned with Bradford method. According to our studies results; cell growth rised in KWJ groups to which KWJ was taken in comparison to the positive control (K2Cr2O7) group at different growing times (1, 3, 5 and 24 hours) (p<0,05). As a result KWJ has a protecting for decrease the oxidative damage and increased cell growing and induced protein synthesis in S. cerevisiae culture.
Keywords: kiwi fruit juice; SDS-PAGE; protein; chromium; oxidative damage; cell growth